On legal pluralism. On the right of Latin American indigenous peoples - Sobrevilla, David (Estudios de Filosofía, 2008)
In what follows I am going to deal almost exclusively with classical pluralism with regard to a very specific problem: how to solve the situation that originated when the European invasion and the subsequent conquest left us as one of its consequences the anomalous coexistence in the same territory of two rights: the official, written and come from Europe, and indigenous rights, which were oral and autochthonous? We will see that at first it was simply chosen to deny indigenous rights in the name of the tax: with more caution in the colonial era and more radically in independence and during the republican era (I). How in a second moment the project of assimilating indigenous peoples and their right into a homogeneous nation-state arose (II). Subsequently, it has been proposed to recognize the right of Latin American indigenous peoples in a plural state (III). We will then examine what the rights of Latin American indigenous peoples may consist of and some of the difficulties they entail (IV). Next, we will recount the Colombian experience to articulate official law and indigenous rights in a plural state (V). [Fragment]